The role of goal orientations in students’ perceptions of classroom assessment in higher education - Kaur, Amrita; Noman, Mohammad; Awang Hashim, Rosna (Routledge, 2018)
Students’ perception of assessment methods plays a significant role in determining their effort towards learning and their assessment tasks. Similar to the role of goal orientation in predicting students’ classroom learning, this study aims to examine how students’ goal orientations influence their perception of classroom assessments. Using a qualitative research design, the data was collected from 41 students enrolled in master’s degree programme at a public university in northern Malaysia, using reflection notes and semi-structured interviews. Data was analysed using a typo logical approach to inductively develop the categories. The findings demonstrated that perception of mastery goal oriented students considerably contrasted with those with performance goal orientation. The distinctions in perception is discussed under four categories: assessment as a process or product, preferences for modes, reasons for effort and feeling and emotions. The implications of the findings are discussed for higher education practitioners.